The influence of nurse allocated triage category on the care of patients with sepsis in the emergency department: A retrospective review. (June 2021) - Nevill, Alexandra; Kuhn, Lisa; Thompson, John; Morphet, Julia
Abstract: Background: 'Gold standard' sepsis care encompasses the recognition and treatment of sepsis within one hour of emergency department (ED) presentation. Early treatment of patients with sepsis reduces mortality. The aim of this study was to examine the effect that the nurse allocated Australasian Triage Scale (ATS) Category allocation had on ED patient treatment for severe sepsis and septic shock. Methods: A two-year retrospective observational cohort study from a single major metropolitan ED, including all patients with severe sepsis or septic shock. Results: Sixty patients were included in this study. Sepsis was recognised at triage for the majority of patients (n = 38, 63%), and most were allocated an ATS Category Two (n = 39). Almost half of the patients received all elements of the sepsis bundle within one hour of arrival (n = 27, 45%). Patients allocated an ATS Category One or Two had a shorter time to lactate collection (p = 0.003), blood culture procurement (p = 0.009) and intravenous antibiotic administration (p = 0.021) compared with patients who were allocated ATS Category Three or Four. Conclusions: Most patients presenting with sepsis were recognised by the triage nurse and allocated a high acuity ATS category accordingly. As sepsis is a time-critical condition and a high acuity triage allocation reduces time to treatment, we recommend all Australian EDs should implement a standard approach to sepsis triage by allocating an ATS Category of One or Two to all patients suspected of having sepsis, thus reflecting the urgency of their disease.